2008
DOI: 10.1093/nar/gkn990
|View full text |Cite
|
Sign up to set email alerts
|

A novel chair-type G-quadruplex formed by a Bombyx mori telomeric sequence

Abstract: Recently, the human telomeric d[TAGGG(TTAGGG)3] sequence has been shown to form in K+ solution an intramolecular (3+1) G-quadruplex structure, whose G-tetrad core contains three strands oriented in one direction and the fourth in the opposite direction. Here we present a study on the structure of the Bombyx mori telomeric d[TAGG(TTAGG)3] sequence, which differs from the human counterpart only by one G deletion in each repeat. We found that this sequence adopted multiple G-quadruplex structures in K+ solution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 44 publications
(70 reference statements)
0
81
0
2
Order By: Relevance
“…The Bom17 oligonucleotide reportedly adopts an anti-parallel G-quadruplex fold [21] in equilibrium with a hairpin duplex [22]. The anti-parallel G-quadruplex CD profile (Fig.…”
Section: Influence Of Fluorophores On Oligonucleotide Structuresmentioning
confidence: 98%
See 1 more Smart Citation
“…The Bom17 oligonucleotide reportedly adopts an anti-parallel G-quadruplex fold [21] in equilibrium with a hairpin duplex [22]. The anti-parallel G-quadruplex CD profile (Fig.…”
Section: Influence Of Fluorophores On Oligonucleotide Structuresmentioning
confidence: 98%
“…FRET melting experiments have been used previously to characterise the interaction of ligands with oligonucleotides [21,22] The accessible temperature range of real-time thermocyclers is 25e95 C. For FRET melting assays, therefore, the melting temperature of the oligonucleotide in the absence of ligand should ideally be around 50 C. A lower T m would lead to incomplete folding at low temperature, whereas a higher T m would prevent the analysis of the transitions obtained with highly stabilising ligands. Our analyses of the K þ concentration dependence of melting of the dye-labelled G-quadruplex-forming oligonucleotides indicated that 1 mM K þ is optimal for analysis of ligand effects on the stability of these oligonucleotides.…”
Section: Influence Of K þ Concentration On G-quadruplex Stabilitymentioning
confidence: 99%
“…Indeed, the topology described by loop progression (ÀlÀlÀl) had been proposed to be defined by groove width combinations (wnwn) in 2007 [10] before its experimental confirmation. [23] 9. Prevalence of loop type combinations [24], (b) 1XAV [25], (c) 2LEE [26], (d) 2LBY [27], (e) 2KYP [28], (f) 2LPW [29], (g) 2KZE [30] and (h) 2LXQ [31] with examples determined in crowded conditions (2LD8, [32]) and in dimeric form stacked 5 0 -5 0 (2LE6, [33] and 2LXV, [31]).…”
Section: Implications Of the Descriptor On Topologymentioning
confidence: 99%
“…A greater number of stacking possibilities have been experimentally determined in this group: (a) (ÀlÀlÀl) as a two-stacked topology [23], (b) (+l+l+l) as the two-stacked 2KM3 [41] and 148D [42], (c) (Àld+l) as the four-stacked 201D [22], the three-stacked 143D [16] and the two-stacked 2KF8 [20] and 2KKA [21], and (d) (+ldÀl) as the twostacked 2KOW [43].…”
Section: Implications Of the Descriptor On Topologymentioning
confidence: 99%
See 1 more Smart Citation